2019
DOI: 10.3390/molecules24142598
|View full text |Cite
|
Sign up to set email alerts
|

Oil Extraction and Evaluation from Yellow Horn Using a Microwave-Assisted Aqueous Saline Process

Abstract: This study investigates an aqueous salt process (ASP) combined with microwave-assisted extraction (MAE) for the seed oil extraction from yellow horn (Xanthoceras sorbifolium Bunge). The NaCl concentration in the oil extraction process affected the oil extraction yield. Box–Behnken design (BBD) and response surface methodology (RSM) were used to optimize the extraction process. The optimal operating parameters were: 24 g/L NaCl, 300 W microwave power, 4:1 water to material ratio, an 80 min extraction time, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…As seen in Table 2 , yellow horn oil contained mainly oleic and linoleic acids with 33.40% and 44.81%, respectively. In addition, it also contained 4.06% of nervonic acid, which was consistent with the study by Huang [ 9 ] et al This indicated that the SF-CO 2 extraction did not change the fatty acid composition of the yellow horn oil.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As seen in Table 2 , yellow horn oil contained mainly oleic and linoleic acids with 33.40% and 44.81%, respectively. In addition, it also contained 4.06% of nervonic acid, which was consistent with the study by Huang [ 9 ] et al This indicated that the SF-CO 2 extraction did not change the fatty acid composition of the yellow horn oil.…”
Section: Resultssupporting
confidence: 91%
“…Nervonic acid can repair damaged brain nerves, thus preventing brain nerve aging and keeping them active [ 8 ]. It also contains a variety of active substances such as flavonoids and polyphenols [ 9 ]. Therefore, yellow horn oil plays a role in preventing disease.…”
Section: Introductionmentioning
confidence: 99%
“…After this point, the extraction yields moderately decreased and remained constant (~2.70%) with a continuous increase in the ratio from 4 to 5 mL/g (p ≤ 0.05). This may be because the oil-water separation effect was minimized with a high ratio of water to material [44]. The results suggested that a suitable amount of saline solution can easily achieve the maximum extraction yield of the target compounds.…”
Section: Effect Of the Liquid-to-solid Ratiomentioning
confidence: 97%
“…This value significantly decreased when using NaCl above this concentration (p ≤ 0.05). This could be because inorganic salt increases the polarity difference between oil and water, thereby reducing the oil's solubility in the water and enhancing the process's salt-assisted effect [44]. In other words, a higher concentration of NaCl can cause a salting-out effect that leads to protein aggregation and precipitation.…”
Section: Effect Of the Concentration Of Naclmentioning
confidence: 99%
“…Recently, many studies with respect to new types of oil have been carried out. They usually focus on the preparation methods, physicochemical properties, antioxidant properties, nutritional properties, and applications of oils [22][23][24][25][26][27][28][29][30][31]. As a result, the information about tocols in new types of vegetable oil is severely scarce.…”
Section: Introductionmentioning
confidence: 99%